2002
DOI: 10.1177/107110070202300304
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Entrapment in Painful Heel Syndrome

Abstract: Subcalcaneal heel pain is one of the most common foot ailments, yet the exact etiology is still controversial. Nerve entrapment has been suggested as one of the possible causes of this painful condition in recalcitrant cases. The purpose of this study is to determine the role of nerve entrapment in painful heels. Twenty patients with heel pain (25 heels) were compared with an age and body mass index-matched control population using electrodiagnostic methods. The results of the study revealed 22 heels (88%) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 14 publications
0
15
0
2
Order By: Relevance
“…39 Many factors have been purported to cause plantar heel pain, including overuse, biomechanical derangements, inflammatory arthritis, stress fractures, nerve entrapment, and defective running shoe construction. 8,32,42 Amis et al 3 found that 78% of patients with painful heels had ankle dorsiflexion limitations of at least 5°. Kibler et al 26 noted that 90% of running athletes with plantar fasciitis had either a lack of 5°dorsiflexion beyond neutral on the affected side, or a lack of 10°or more dorsiflexion compared to the nonaffected side.…”
mentioning
confidence: 99%
“…39 Many factors have been purported to cause plantar heel pain, including overuse, biomechanical derangements, inflammatory arthritis, stress fractures, nerve entrapment, and defective running shoe construction. 8,32,42 Amis et al 3 found that 78% of patients with painful heels had ankle dorsiflexion limitations of at least 5°. Kibler et al 26 noted that 90% of running athletes with plantar fasciitis had either a lack of 5°dorsiflexion beyond neutral on the affected side, or a lack of 10°or more dorsiflexion compared to the nonaffected side.…”
mentioning
confidence: 99%
“…Postoperativ Anlegen einer Unterschenkelschiene oder Orthese in Neutralstellung. Hinweise auf ein Nervenengpasssyndrom sind über-wiegend belastungsabhängige Beschwerden an der medioplantaren Ferse und typischerweise verstärkte Beschwerden beim morgendlichen Aufstehen oder nach einer längeren Ruhepause [7,12]. Gelegentlich kann es auch zu Schmerzen im Ruhezustand kommen.…”
Section: Operationstechnikunclassified
“…Der erste Ast des Nervus plantaris lateralis hat rein motorische Qualitäten und versorgt den Musculus flexor digitorum brevis, den Musculus quadratus plantae und den Musculus abductor digiti quinti [10]. Typische Prädilektionsstellen für eine Nervenkompression sind der Rand der tiefen Faszie des Musculus abductor hallucis, die mediale Kalkaneusregion (Region des plantaren Fersensporns) sowie die Region zwischen dem Musculus abductor hallucis und dem medialen Kopf des Musculus quadratus plantae.Hinweise auf ein Nervenengpasssyndrom sind über-wiegend belastungsabhängige Beschwerden an der medioplantaren Ferse und typischerweise verstärkte Beschwerden beim morgendlichen Aufstehen oder nach einer längeren Ruhepause [7,12]. Gelegentlich kann es auch zu Schmerzen im Ruhezustand kommen.…”
unclassified
“…2 Nerve entrapment syndrome has previously been considered only in cases with intractable heel pain, but it may play a role in the early phases of painful heel syndrome. 3 Diagnosis of the nerve entrapment is made on clinical grounds. Early morning pain is uncommon with isolated nerve entrapment.…”
mentioning
confidence: 99%